THE EFFECT OF CROSSWORD PUZZLE GAME ON STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL - MAHARANI, MAHYA (BRIGHT VISION Journal of Language and Education, 2021)
The aim of this research was to find out whether there was a significant effect of using crossword puzzle game on students‟ reading comprehension of narrative text at the eighth grade of Junior High School conducted in SMPN 3 Bambel in academic year 2020/2021. A quantitative research with quasi-experimental design was to conduct in this research. Through this design, 40 sample students chosen by purposive sampling and divided into two groups, namely experimental class and control class with each class had a total number of 20. In collecting the data, multiple choices were used as the instrument for pre-test and post-test. In giving treatment, experimental class was taught by Crossword Puzzle Game, while control class by teaching center learning. The data collected was analyzed using SPSS v.20. The results showed that the mean score of post-test in experimental class (85) was higher than Control class (75.5). Thus, the result of t-test also showed (2.656)> (2.024), and the Sig. (2-tailed) = 0.011< α =  0.05  which  means  there  was  significant  difference  result  between  the  use  of Crossword Puzzle Game and without Crossword Puzzle Game. It means      is accepted because sig. < α = 0.05 and      is rejected. Further, the result of the analysis showed that teaching reading in narrative text by using Crossword Puzzle Game is effective. Thus, Crossword Puzzle Game has significant effect on students‟ reading comprehension of narrative text at the eighth grade of SMP N 3 Bambel. Key words: Crossword Puzzle Game, Reading Comprehension, Junior High School